Faithful completely reducible representations of modular Lie algebras. Issue 6 (3rd June 2017) - Barnes, Donald W.
ABSTRACT: Let L be a Lie algebra of dimension n over a field F of characteristic p >0. I prove the existence of a faithful completely reducible L -module of dimension less than or equal to p n 2 − 1 .